Proceedings of the 26th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2020
DOI: 10.1145/3394486.3403136
|View full text |Cite
|
Sign up to set email alerts
|

Mining Persistent Activity in Continually Evolving Networks

Abstract: Frequent pattern mining is a key area of study that gives insights into the structure and dynamics of evolving networks, such as social or road networks. However, not only does a network evolve, but often the way that it evolves, itself evolves. Thus, knowing, in addition to patterns' frequencies, for how long and how regularly they have occurred-i.e., their persistence-can add to our understanding of evolving networks. In this work, we propose the problem of mining activity that persists through time in conti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…SEDANSPOT [11] identifies edge anomalies based on edge occurrence, preferential attachment, and mutual neighbors. PENminer [12] explores the persistence of activity snippets, i.e., the length and regularity of edge-update sequences' reoccurrences. F-FADE [13] aims to detect anomalous interaction patterns by factorizing their frequency.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…SEDANSPOT [11] identifies edge anomalies based on edge occurrence, preferential attachment, and mutual neighbors. PENminer [12] explores the persistence of activity snippets, i.e., the length and regularity of edge-update sequences' reoccurrences. F-FADE [13] aims to detect anomalous interaction patterns by factorizing their frequency.…”
Section: Related Workmentioning
confidence: 99%
“…We use open-source implementations of DENSESTREAM [1] (Java), SEDANSPOT [11] (C++), MIDAS-R [3] (C++), PENminer [12] (Python), F-FADE [13] (Python), DENSEALERT [1] (Java), and ANOMRANK [14] (C++) provided by the authors, following parameter settings as suggested in the original paper. For SPOTLIGHT [2], we used open-sourced implementations of Random Cut Forest [55] and Carter Wegman hashing [56].…”
Section: Appendix a H-cmsmentioning
confidence: 99%
See 1 more Smart Citation
“…PENminer [8] explores the persistence of activity snippets, i.e., the length and regularity of edge-update sequences' reoccurrences. F-FADE [15] aims to detect anomalous interaction patterns by factorizing the frequency of those patterns.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, there is another category of algorithms that aims to detect anomalies using patterns or motifs [8,15,43,38,30,33,55,3,23,29,41,40,35,31,7,20,11]. However, many of these methods require active exploration of patterns or snippets, increasing memory and time requirements.…”
Section: Introductionmentioning
confidence: 99%